Paradigm of the Educational Curriculum Perspective of the Qur'an - Irwan Suanto; Kadar M. Yususf (CV. Publikasi Indonesia, 2026)
This article discusses the paradigm of the educational curriculum in the perspective of the Qur'an as an epistemological, philosophical, and pedagogical foundation for the development of the contemporary education system. This study is motivated by the problems of dehumanization, fragmentation of knowledge, and materialistic orientation that color the modern curriculum, so that an alternative framework that is more integrative and centered on the development of the whole human being (insān kāmil) is needed. Using the literature research method and the maudhū'ī tafsir approach, this article examines the verses of the Qur'an related to educational goals, learning processes, student characters, and scientific structure. The results of the study show that the Qur'anic curriculum paradigm is built on the principles of monotheism, the integration of knowledge and values, moral development, and the strengthening of spiritual and social awareness. The paradigm offers a reorientation of educational goals, a tadabbur-based learning model, as well as a relevant character evaluation approach to answer the challenges of 21st century education. Thus, the Qur'anic perspective education curriculum has the potential to be a normative and practical foundation in formulating a holistic, humanistic, and civilized curriculum. This article recommends the need for further research related to the implementation of the Qur'ani curriculum at various levels of education in Indonesia so that this paradigm can be operationalized more effectively in the context of modern educational praxis.